Calcium looping post-combustion CO2 capture in sugarcane bagasse fuelled power plants. (September 2021) - Neto, Sudá; Szklo, Alexandre; Rochedo, Pedro R.R.
Highlights: Biomass-fired calcium looping is a promising post-combustion CO2 capture technology. The technology has the potential to outperform amine-based chemical absorption. Bio-CaL is more efficient in water use and allows for more flexibility in operation. Sugarcane bagasse demonstrates advantages over other biomasses for such systems. Continued R&D and system scale-up is recommended. Abstract: Biomass energy conversion with carbon capture and storage (BECCS) can lead to the net removal of CO2 from the atmosphere. Calcium looping (CaL) is a promising carbon capture process for existing or greenfield capture-ready biomass-fired plants. This paper investigates the technical and economic performance of BECCS using CaL systems as a retrofit to Brazilian cogeneration plants fuelled with sugarcane bagasse. Bagasse-fired cogeneration plants integrated with CaL were compared with their correspondent base plant without CO2 capture and with chemical absorption using Cansolv solvent, the current benchmark for post-combustion CO2 capture. Key parameters such as CO2 removal potential, water use, added plant footprint, and levelized energy cost (LCOE) were analyzed. Although the Bio-CaL alternative is not cost-effective compared to Cansolv for a first of a kind plant, the assessed system presents competitive advantages in operational flexibility, energy efficiency, and electricity surplus in comparison with the chemical absorption route. For future plants, economic results are promising and can match those of more conventional technologies. Therefore, investments in pilot size biomass-fired CaL units should be stimulated to promote learning and allow the implementation of large-scale plants that would likely operate with similar costs but greater flexibility and thermal efficiency than the current more mature CO2 capture technologies.